Xylochemicals and where to find them. Issue 78 (15th September 2021) - Groß, Jonathan; Grundke, Caroline; Rocker, Johannes; Arduengo, Anthony J.; Opatz, Till
Abstract : More than 100 useful 'xylochemicals' and their natural origins are offered combined with an overview of comparative petro- and xylochemical approaches to synthetic chemistry. Abstract : This article surveys a range of important platform and high value chemicals that may be considered primary and secondary 'xylochemicals'. A summary of identified xylochemical substances and their natural sources is provided in tabular form. In detail, this review is meant to provide useful assistance for the consideration of potential synthetic strategies using xylochemicals, new methodologies and the development of potentially sustainable, xylochemistry-based processes. It should support the transition from petroleum-based approaches and help to move towards more sustainability within the synthetic community. This feasible paradigm shift is demonstrated with the total synthesis of natural products and active pharmaceutical ingredients as well as the preparation of organic molecules suitable for potential industrial applications.